Chronic Recurrent Multifocal Osteomyelitis: An Unusual Cause of “Aches and Pains” - Jamal, Ahmad; John, Biju; Awariwar, Mahesh; Dalal, Shamsher; Singh, Daljit (Journal of Nepal Paediatric Society, 2018)
Children are often brought to the paediatric out-patient department with non specific aches and pains. Though the majority of them have only a benign diagnosis, some may harbour rare conditions like chronic recurrent multifocal osteomyelitis (CRMO). Case: We describe a 11 year old girl who presented with migratory pain across various parts of hip and lower limbs without any significant signs. After six months of OPD visits, she was diagnosed to have CRMO following an incidental X-ray which led to a musculoskeletal MRI. Conclusion: CRMO is a rare auto-inflammatory disorder which must be kept in mind when encountering a relatively healthy child with poorly defined limb pains along with paucity of signs.